2010
DOI: 10.1097/fbp.0b013e328340a050
|View full text |Cite
|
Sign up to set email alerts
|

Effects of acute and repeated nicotine administration on delay discounting in Lewis and Fischer 344 rats

Abstract: Biological differences may underlie individual differences in impulsive behavior, such as choice for a smaller, more immediate reinforcer over a larger, more delayed reinforcer. Repeated exposure to drugs of abuse may have differing effects on such behavior. To evaluate acute and repeated effects of nicotine on impulsive choice, two strains of rats that have been shown to differ in impulsive choice were tested in a delay-discounting paradigm. Eight Lewis and eight Fischer 344 rats were allowed to choose betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

12
92
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(106 citation statements)
references
References 60 publications
12
92
2
Order By: Relevance
“…It could be said that in adjusting to the transition from the ascending to the descending presentation order of delays, the LEWs did so more rapidly than the F344s, choosing the LL lever at higher proportions during most delays to LLR. This result is in dispute with previous findings (Anderson & Diller, 2010;Anderson & Woolverton, 2005;Huskinson et al, 2012;Madden et al, 2008;Stein et al, 2012) that showed more impulsivity in the LEWs; the assertion that the LEWs choose more impulsively than the F344s is not supported by the present study, challenging this strain difference and confirming that it may be due to procedural issues (Stein et al, 2012) and the analytical tools used to characterize impulsive choice (Madden & Johnson, 2010).…”
Section: Discussioncontrasting
confidence: 57%
See 3 more Smart Citations
“…It could be said that in adjusting to the transition from the ascending to the descending presentation order of delays, the LEWs did so more rapidly than the F344s, choosing the LL lever at higher proportions during most delays to LLR. This result is in dispute with previous findings (Anderson & Diller, 2010;Anderson & Woolverton, 2005;Huskinson et al, 2012;Madden et al, 2008;Stein et al, 2012) that showed more impulsivity in the LEWs; the assertion that the LEWs choose more impulsively than the F344s is not supported by the present study, challenging this strain difference and confirming that it may be due to procedural issues (Stein et al, 2012) and the analytical tools used to characterize impulsive choice (Madden & Johnson, 2010).…”
Section: Discussioncontrasting
confidence: 57%
“…For instance, studies using an autoshaping technique (Brown & Jenkins, 1968) to establish lever pressing for food found that the LEWs acquired that behavior more rapidly and performed it at higher rates than the F344s (Kearns, Gomez-Serrano, Weiss, & Riley, 2006); similar results were documented by Anderson and Elcoro (2007) using a tandem fixed-ratio one, fixed-time 20 s schedule of reinforcement to establish lever pressing for food. Moreover, studies of impulsive choice in LEWs and F344s have shown steeper discounting functions for the former than for the latter strain of rats (e.g., Anderson & Diller, 2010;Anderson & Woolverton, 2005;Huskinson, Krebs, & Anderson, 2012;Madden, Smith, Brewer, Pinkston, & Johnson, 2008). Nonetheless, the generality of this finding has been compromised by research that failed to show differences in discounting functions between LEWs and F344s (e.g., Stein et al, 2012;Wilhelm & Mitchell, 2009).…”
mentioning
confidence: 70%
See 2 more Smart Citations
“…by inhibiting cortical regulation mechanisms or by impacting the sensitivity of the brain's reward system. 52,78 Previous studies not included in our review found that (i) those seeking smoking cessation had lower discount rates, creating potential selection bias that is unaddressed in experiments analysing voluntary participants, 25 and (ii) timediscounting significantly decreased at a 12-month follow-up among smokers who successfully quit. 79 Conversely, there is also evidence that short-term withdrawal from smoking increases time-discounting.…”
Section: Discussionmentioning
confidence: 94%